Discussing the ‘Grandmother Hypothesis’ - Horský, Jan (Dějiny – teorie – kritika, 2021)
The ‘grandmother hypothesis’ is connected with a distant evolutionary event of the emergence of menopause in human females and can be put to the test by (historical) demographic data for European society of the Early Modern Age and the Modern Age. Comparisons of case studies and micro-analytic probes into historical demography and cultural history of the 17th–19th c. allow us to draw certain conclusions: where the ‘grandmother effect’ (i.e. shorter inter-birth intervals in daughters or daughters-in-law alongside with a lower rate of infant and child mortality of grandchildren, in other words, fitter grandchildren) can be proven from a statistical point of view, in most cases, the effect is significantly weaker than the effect of other factors which influence infant and child mortality. Grandmothers participating in the care of their grandchildren may not have been a ‘cultural pattern’ (reflected as such by its actors), in any case, not to the degree to which a ‘cultural pattern’ was reflected in a regionally specific structure of households or the use of midwives’ services. At least in the European populations of the 17th–19th c., we can find other institutions which seem to have had a stronger impact on infant and child mortality than grandmothers taking care of their grandchildren. In this period, the grandmother effect was geographically dispersed and, at least in some cases, linked to particular social groups or segments of society (in the Czech sample, for instance, the effect was linked to lower social classes). If the grandmother effect increasing the fitness of grandchildren is more pronounced with maternal grandmothers (which is yet to be generally proven), we must ask why cultural evolution ‘chose’ the adaptively less favourable option of patrilinear structure of family households. An example of such structure can be found in a consistent patrilocality of marriages and patrilineality of the family structure in classical antiquity, which, in the European environment, has survived until recently southeast of the so-called Hajnal Line. Research in demography and cultural history of the 17th–19th c. European society seems to strongly support the following claim, which from the perspective of evolutionary anthropology or evolutionary biology is merely a hypothetical supposition: The ‘grandmother effect’ may have been the cause of the menopause as an evolutionary adaptation. Nonetheless, while this phenomenon has been present in human population since ancient times (prehistory or antiquity), it was merely one of many mutually complementary, alternative, and more or less adaptive (i.e. fitness-increasing) forms of infant and child care.